Baseline severity and the prediction of placebo response in clinical trials for alcohol dependence: A meta‐regression analysis to develop an enrichment strategy. (21st August 2021) - Scherrer, Bruno; Guiraud, Julien; Addolorato, Giovanni; Aubin, Henri‐Jean; de Bejczy, Andrea; Benyamina, Amine; van den Brink, Wim; Caputo, Fabio; Dematteis, Maurice; Goudriaan, Anna E.; Gual, Antoni; Kiefer, Falk; et al.
Abstract: Background: There is considerable unexplained variability in alcohol abstinence rates (AR) in the placebo groups of randomized controlled trials (RCTs) for alcohol dependence (AD). This is of particular interest because placebo responses correlate negatively with treatment effect size. Recent evidence suggests that the placebo response is lower in very heavy drinkers who show no "spontaneous improvement" prior to treatment initiation (high‐severity population) than in a mild‐severity population and in studies with longer treatment duration. We systematically investigated the relationship between population severity, treatment duration, and the placebo response in AR to inform a strategy aimed at reducing the placebo response and thereby increasing assay sensitivity in RCTs for AD. Methods: We conducted a systematic literature review on placebo‐controlled RCTs for AD.We assigned retained RCTs to high‐ or mild‐severity groups of studies based on baseline drinking risk levels and abstinence duration before treatment initiation. We tested the effects of population severity and treatment duration on the placebo response in AR using meta‐regression analysis. Results: Among the 19 retained RCTs (comprising 1996 placebo‐treated patients), 11 trials were high‐severity and 8 were mild‐severity RCTs. The between‐study variability in AR was lower in the high‐severity than in the mild‐severity studies (interquartile range: 7.4% vs. 20.9%). The AR in placebo groups was dependent on population severity ( p  = 0.004) and treatment duration ( p  = 0.017) and was lower in the high‐severity studies (16.8% at 3 months) than the mild‐severity studies (36.7% at 3 months). Conclusions: Pharmacological RCTs for AD should select high‐severity patients to decrease the magnitude and variability in the placebo effect and and improve the efficiency of drug development efforts for AD. Abstract : Using a meta‐regression analysis, we investigated the effect of baseline population severity and treatment duration on the placebo response in alcohol abstinence rate in 19 randomized controlled trials (RCTs) conducted in the treatment of alcohol dependence (AD). The placebo response was significantly lower in the high‐severity group of studies and in studies with longer treatment duration. Future pharmacological RCTs for AD should consider the selection of high‐severity patients to decrease the placebo effect and increase assay sensitivity.